Sonographic measurement of inferior vena cava diameter in assessment of volume status in pediatric shock: A prospective observational study. - Dr. Vidhyadhar V; Dr. Sowmya N; Dr. Manu Srinivas H; Dr.Muralidhar G; Basavaraja G V (Student's Journal of Health Research Africa)
Background Accurate assessment of intravascular volume status in pediatric shock remains a clinical challenge, often relying on subjective and invasive methods. Bedside ultrasonography of the inferior vena cava (IVC) has emerged as a promising, non-invasive modality to estimate volume status. This study aimed to evaluate the IVC diameter and IVC-to-aortic (IVC/Ao) ratio as objective indicators of hypovolemia in children using ultrasound.